2020
DOI: 10.1177/1535370220943124
|View full text |Cite
|
Sign up to set email alerts
|

Early myocardial injury biomarkers in diabetic hyperlipidemic rats: Impact of 10-dehydrogingerdione and vitamin D3

Abstract: Hyperlipidemia represents a major risk factor for cardiovascular diseases leading to myocardial injury. The present study aimed to illustrate the myocardial injury induced in a diabetic hyperlipidemic rat model and the effect of vitamin D3, 10-DHGD intake either individually or in combination form. Male albino rats were selected for the study, received alloxan, hypercholesterolemic diet, and categorized into four groups. The first one (DHC), received hypercholesterolemic diet only and referred to as control. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 78 publications
(96 reference statements)
1
1
0
Order By: Relevance
“…70 The results demonstrated a significant rise in total cholesterol, triacylglycerol l, LDL-C, and VLDL-C levels and a marked decline in HDL-C levels in the positive control group compared to the negative control group at the end of the experimental period. These findings are consistent with those in other studies, 71,72 which reported that the levels of triacylglycerol, total cholesterol, LDL-C, and VLDL-C were significantly increased, and the HDL-C levels were declined considerably in diabetic hyperlipidemic rats because of the damaging effect of streptozotocin on b-cells and HFD consumption that results in reduced insulin secretion, hyperglycemia, and hyperlipidemia, while the groups treated with bee venom using both doses (0.5 and 1.23 mg/kg) and the combined therapy (metformin and atorvastatin) showed a significant decline in total cholesterol, triacylglycerol, LDL-C, VLDL-C levels, and a significant elevation in HDL-C levels in comparison to the positive control group at the end of the experimental period. The results are supported by other studies, 73,74 which revealed the ability of bee venom to alleviate lipid profile abnormalities through increasing insulin secretion and sensitivity in experimental animal models.…”
Section: Groupssupporting
confidence: 94%
“…70 The results demonstrated a significant rise in total cholesterol, triacylglycerol l, LDL-C, and VLDL-C levels and a marked decline in HDL-C levels in the positive control group compared to the negative control group at the end of the experimental period. These findings are consistent with those in other studies, 71,72 which reported that the levels of triacylglycerol, total cholesterol, LDL-C, and VLDL-C were significantly increased, and the HDL-C levels were declined considerably in diabetic hyperlipidemic rats because of the damaging effect of streptozotocin on b-cells and HFD consumption that results in reduced insulin secretion, hyperglycemia, and hyperlipidemia, while the groups treated with bee venom using both doses (0.5 and 1.23 mg/kg) and the combined therapy (metformin and atorvastatin) showed a significant decline in total cholesterol, triacylglycerol, LDL-C, VLDL-C levels, and a significant elevation in HDL-C levels in comparison to the positive control group at the end of the experimental period. The results are supported by other studies, 73,74 which revealed the ability of bee venom to alleviate lipid profile abnormalities through increasing insulin secretion and sensitivity in experimental animal models.…”
Section: Groupssupporting
confidence: 94%
“…Furthermore, serum cholesterol and triglyceride levels decreased significantly in GLB- and GLB/vitamin D-treated diabetic groups than in the diabetic untreated animals, which was consistent with previous studies. 34 , 35 GLB has a hypolipidemic effect by inhibiting or reducing cholesterol biosynthesis, reducing fatty acid synthesis, and/or promoting the formation of triglyceride precursors such as acetyl CoA and glycerol phosphate. 25 On the other hand, Vitamin D can improve hyperlipidemia either indirectly by stimulating VDR, which helps in reducing acetylated low-density lipoprotein cholesterol uptake, or directly by stimulating lipogenesis through the activation of lipoprotein lipase in adipocytes.…”
Section: Discussionmentioning
confidence: 99%